Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Pada Kantor Imigrasi Kelas II Non Tpi Meulaboh - Iir Maya Sari (Universitas Teuku Umar, 2023)
This study aims to determine the services provided by the immigration office to the community and how much influence the quality of immigration office services has on community satisfaction. This study uses a quantitative descriptive method. The population in this study amounted to 400 people. While taking samples using Aricunto's opinion with a technique that contains if the population is < 100, then all of them will be sampled, but if > 100, then a sample of 10-15% or 20-25% is taken. Convenience sampling to obtain a sample of 50 people. Technique data collection used is observation, questionnaires, and literature study. The results of this study are that the services at the Bengkalis Immigration Office have been appropriately fulfilled based on the provisions of the central government. Then the service quality of the Bengkalis Immigration Office significantly affects the level of community satisfaction, with an influence percentage of 13.1%, and other variables influence the remaining 86.9%.